A comprehensive review on miR-153: Mechanistic and controversial roles of miR-153 in tumorigenicity of cancer cells - Yousefnia, Saghar (Frontiers in Oncology, 2022)
miRNAs play a crucial role in regulating genes involved in cancer progression. Recently, miR-153 has been mainly well-known as a tumor suppressive miRNA modulating genes in proliferation, metastasis, EMT, angiogenesis and drug resistance ability of a variety types of cancer. Mechanistic activity of miR-153 in tumorigenicity has not been fully reviewed. This manuscript presents a comprehensive review on the tumor suppressive activity of miR-153 as well as introducing the controversial role of miR-153 as an oncogenic miRNA in cancer. Furthermore, it summarizes all potential non-coding RNAs such as long non-coding RNAs (LncRNAs), transcribed ultra-conserved regions (T-UCRs) and circular RNAs (CircRNAs) targeting and sponging miR-153. Understanding the critical role of miR-153 in cell growth, metastasis, angiogenesis and drug resistance ability of cancer cells, suggests miR-153 as a potential prognostic biomarker for detecting cancer as well as providing a novel treatment strategy to combat with several types of cancer.